Design Of Computer Network Communication In JASDAM II Sriwijaya With Top-Down Method - Alvian Pratama; Aan Restu Mukti; Fatoni; Zaid Amin (ARRUS Journal of Engineering and Technology, 2024)
The need for reliable and extensive network infrastructure in a military environment, especially in Jasdam II Sriwijaya, is becoming increasingly important along with the security tasks and challenges faced. This research aims to design a network that meets military standards and performance by applying the Top-Down method. The Top-Down method in the context of network design, along with network needs analysis in a military environment. Through this approach, this research aims to strengthen operations and expand the network in Jasdam II Sriwijaya. The research methodology includes data collection on network needs, needs analysis, Top-Down design, implementation, and testing. The expected results of this research are the design of a network structure at 3 locations that are in accordance with well-defined military needs, as well as expanding network communications in a military environment, measuring how well the network is using the QoS method. This research provides optimal network infrastructure development in JASDAM II Sriwijaya, with the potential for a wider scale.